2021
DOI: 10.3390/ma14237343
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Micromechanical Properties and Tribological Behavior of WE43 Magnesium Alloy after Deep Cryogenic Treatment Combined with Precipitation Hardening

Abstract: This study investigated the micromechanical and tribological properties of WE43 alloy (Mg-Y-Nd-Zr) alloy subjected to cryogenic treatment and precipitation hardening. Microindentation tests were carried out in the range of load from 100 to 1000 mN. The introduction of deep cryogenic treatment (DCT) was shown to increase hardness and Young’s modulus, and reduce the total indentation work. As the load set during the tests increased, a gradual decrease in the measured values was observed, indicating a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…REE-Mg has been found to have superior mechanical and corrosion resistance compared to other Mg alloys, according to [20]. The service life of a Mg alloy can be extended through additional heat treatment by varying the temperature and holding time [21]. It has also been reported that alloying Nd and Gd increases Mg castability and precipitate strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…REE-Mg has been found to have superior mechanical and corrosion resistance compared to other Mg alloys, according to [20]. The service life of a Mg alloy can be extended through additional heat treatment by varying the temperature and holding time [21]. It has also been reported that alloying Nd and Gd increases Mg castability and precipitate strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…and Fe and Ni in amounts exceeding 0.005% wt. are the most harmful impurities affecting the corrosion resistance and plasticity of the alloy) [11], optimization of its chemical composition [12][13][14], preparation methods [2], heat treatment [15][16][17][18][19][20], plastic forming [21,22], and surface modification, including chromium plating, TiN, CrN, AlN aluminum, and titanium coatings; and coatings made of calciumphosphate compounds (Ca-P) to obtain better mechanical, corrosion, and tribological properties [23].…”
Section: Introductionmentioning
confidence: 99%